2010
DOI: 10.1097/mou.0b013e328333ac01
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum neurotoxin A for benign prostatic hyperplasia

Abstract: We should recognize that, at present, this therapy is still experimental. Although the results of the clinical studies are encouraging, the level of evidence is low. Clearly, we need large-scale, clinical, placebo-controlled, randomized studies, including long-term surveillance to document the evidence of this therapy and, eventually, to register BoNT-A for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…However, abundance of adrenergic and muscarinic receptors and nerve fibers suggests that the autonomic nervous system may play a role in the growth and secretory function of the gland [74]. It has been also found that a subtype of muscarinic receptors is present in BPH and was the predominant subtype there.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, abundance of adrenergic and muscarinic receptors and nerve fibers suggests that the autonomic nervous system may play a role in the growth and secretory function of the gland [74]. It has been also found that a subtype of muscarinic receptors is present in BPH and was the predominant subtype there.…”
Section: Discussionmentioning
confidence: 97%
“…Sixty patients received add-on intraprostatic BoNT-A or continued medical therapy The initial results of a two-stage, multicenter, double-blind, randomized, phase II clinical trial of two doses of intraprostatic injection of BoNT-A, funded by NIH, have been reported [74][75][76]. One hundred and thirty-four patients underwent injection of 100 or 300 UI of BoNT-A.…”
Section: Bont-a Effects In Human Prostatementioning
confidence: 99%
“…Botulinum neurotoxin (BoNT) that block at the injection site the release of neurotransmitters, for example, acetylcholine and norepinephrine, from pre‐synaptic nerves, has been demonstrated to affect sympathetic activity in urethral smooth muscle . Injection of BoNT at the level of bladder neck, urethra, and prostate is a novel emerging treatment for LUTS caused by BPH or by voiding dysfunctions characterized by non‐relaxing proximal urethra/bladder neck, however, only a pilot study including eight patients followed‐up for 32 weeks has been published on its use to treat PBND …”
Section: Introductionmentioning
confidence: 99%
“…However, findings from clinical trials have been falling short of expectations. [57][58][59][60][61] Clinical results Clinical results of trials investigating BoNT-A treatment in BPH-associated LUTS are heterogeneous and only partially confirm the effects of BoNT-A observed in experimental studies. The clinical efficacy and safety of different dose ranges of BoNT-A (100 U-300 U) have Nature Reviews | Urology been assessed in several non-placebo-controlled clinical trials.…”
Section: Mechanism Of Actionmentioning
confidence: 89%